2001
DOI: 10.1179/146580101101541822
|View full text |Cite
|
Sign up to set email alerts
|

Dependence on mean stress and stress amplitude of fatigue life of EPDM elastomers

Abstract: This paper describes the dependence on test parameters of the fatigue resistance of EPDM. Fatigue was investigated using dumbbell specimens under load control at 1 Hz until failure. Tests were made in order to create a common Wö hler (S-N) curve while increasing the stress amplitude and also to show the influence of increasing minimum stress at constant stress amplitude on fatigue properties. The results of these tests confirmed the well known amplitude dependence of fatigue life in filled rubbers. An addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Previous research into fatigue of non strain-crystallising elastomers (ethylene propylene diene monomer, EPDM and styrene-butadiene rubber, SBR) by Abraham [20,21] and Alshuth et al [22] suggested that when subjected to uniaxial loading these materials exhibited a limiting value of complex tensile modulus (E*) and this value could be used effectively to design against fatigue failure in rubber components. The concept of using a limiting value of E* was further supported by the research of Jerrams et al [23,24] and Hanley et al [25,26] for EPDM samples, both swollen and unswollen, subjected to equi-biaxial stress cycles.…”
Section: Complex Modulusmentioning
confidence: 99%
“…Previous research into fatigue of non strain-crystallising elastomers (ethylene propylene diene monomer, EPDM and styrene-butadiene rubber, SBR) by Abraham [20,21] and Alshuth et al [22] suggested that when subjected to uniaxial loading these materials exhibited a limiting value of complex tensile modulus (E*) and this value could be used effectively to design against fatigue failure in rubber components. The concept of using a limiting value of E* was further supported by the research of Jerrams et al [23,24] and Hanley et al [25,26] for EPDM samples, both swollen and unswollen, subjected to equi-biaxial stress cycles.…”
Section: Complex Modulusmentioning
confidence: 99%
“…This result was first presented Since the end of the 1990s, number of studies dealing with fatigue of carbon black-filled natural rubber (CB-NR) have been proposed. [2][3][4][5][6][7] Similarly to Ref. [1], fatigue tests performed on CB-NR have revealed an improvement of the fatigue life under non-relaxing uniaxial tension loading conditions; this improvement is classically attributed to strain-induced crystallization (SIC).…”
Section: Introductionmentioning
confidence: 96%
“…As a result, an energy criterion was postulated. Another important effect was highlighted in this research [50,51,52]. As load cycles were accumulated, it was observed that most mechanical properties changed, but in particular the stiffness of specimens changed throughout the full duration of the fatigue tests; an equilibrium material stiffness was never reached.…”
Section: Uniaxial Fatigue Testing Of Non-strain Crystallising Elastomersmentioning
confidence: 69%
“…The dynamic stored energy during cycling of the three sample sets was also evaluated. Previous analyses of uniaxial test data for EPDM found good correlation between the dynamic stored energy in the specimen versus the cycles at failure and its use as a plausible fatigue life predictor was proposed [51][52]. Stressstrain measurements were made periodically throughout the equi-biaxial dynamic tests.…”
Section: Equi-biaxial Fatigue Of Elastomers Subjected To Swellingmentioning
confidence: 99%